TOTAL QUALITY MANAGEMENT IN EFL EDUCATION (Journal of the College of Education for Women, 2019)
The purpose of this study is to identify the extent of the EFL teachers’ implementationoftotal quality management (TQM)principles through teaching English as a foreign language in Iraqi secondary schools.A total of 180 EFL teachers fromsecondary schools in Baghdad during the academic year 2010/ 2011 participated in the study. Data was collected using a scale to identify the extent of implementation of total quality management principles by 140 EFL teachers in their classroom. To support the data collected from the scale,40 teachers were observed by EFL educational supervisors during their lessons. The collected data was analyzed using frequency, means and standard deviation to identify the extent of implementation of (TQM) principles. The weighted means and percentage weights were used to identify the perceptions of EFL educational supervisors. The results showed that the implementation of TQM principles by EFL teachers was moderate overall. The results also showed that the most implemented TQM principles by EFL teachers was (teacher quality) principle. According to observation results the percentage of TQM principles which represents the (high) actual application was (60%), while the (low) actual application was (40%). Thus, the study revealed that EFL teachers need a comprehensive training to implement TQM principles in the secondary schools in Iraq. In the light of the results of the study, the researcher presented conclusions,implications, and suggestions for further study.